Religion as a philosophical matter. Concerns about truth, name, and habitation - Albinus, Lars (De Gruyter, 2016)
The book works out new perspectives for a philosophy of religion that aims beyond the internal questions of rationality within a theological tradition, on the one hand, and the outer criticism of religion from naturalistic quaters, on the other. Instead it places itself within a wider philosophical view in line with groundbreaking thoughts about culture and a basic human 'conditionality' among interwar philosophers such as Ernst Cassirer, Ludwig Wittgenstein, Walter Benjamin, and Martin Heidegger. The book also offers a concrete interpretation of examples of religious phenomena displaying a human world-relation that centers on issues of 'truth', 'name', and 'habitation'. Finally, lines are drawn to Jean-Luc Nancy's current rethinking of Christianity.